2018
DOI: 10.1137/17m1122025
|View full text |Cite
|
Sign up to set email alerts
|

Near-Optimal Bounds for Phase Synchronization

Abstract: The problem of phase synchronization is to estimate the phases (angles) of a complex unit-modulus vector z from their noisy pairwise relative measurements C = zz * + σW , where W is a complex-valued Gaussian random matrix. The maximum likelihood estimator (MLE) is a solution to a unit-modulus constrained quadratic programming problem, which is nonconvex. Existing works have proposed polynomial-time algorithms such as a semidefinite relaxation (SDP) approach or the generalized power method (GPM) to solve it. Nu… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
166
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 117 publications
(166 citation statements)
references
References 43 publications
0
166
0
Order By: Relevance
“…The goal is to recover all the group elements up to a global phase from {g i g −1 j } {(i,j)∈E} where E denotes the index set of available observations. This is called the group synchronization problem, see [1,2,6,7,8,13,35,51] for more details.…”
Section: Group Synchronization Matrix Completion and Monotone Advermentioning
confidence: 99%
See 3 more Smart Citations
“…The goal is to recover all the group elements up to a global phase from {g i g −1 j } {(i,j)∈E} where E denotes the index set of available observations. This is called the group synchronization problem, see [1,2,6,7,8,13,35,51] for more details.…”
Section: Group Synchronization Matrix Completion and Monotone Advermentioning
confidence: 99%
“…Synchronization problems, which aim to recover group elements g i from its relative alignment g i g −1 j (or noisy alignment), are considered on different groups such as phase synchronization [6,51] (corresponding to the group U (1)), Z 2 synchronization [1,7], joint alignment from pairwise differences [13] (corresponding to the cyclic group, i.e., Z/nZ), and general group synchronization problems [35,2]. Many algorithms, some based on convex and nonconvex optimization, are proposed to tackle these problems and proven to work well on group elements retrieval.…”
Section: Related Work and Our Contributionsmentioning
confidence: 99%
See 2 more Smart Citations
“…In this review article, we focus on clustering and community detection (Lowrimore and Manton, 2016), ranking, mixture model and manifold learning. Other applications, such as matrix completion (Keshavan, Montanari and Oh, 2010), phase synchronization (Zhong and Boumal, 2017), image segmentation (Dambreville, Rathi and Tannen, 2006) and functional data analysis (Ramsay, 2016), are not discussed here due to space limitations. Motivated by the fact that data are often collected and stored in distant places, many distributed algorithms for PCA have been proposed (Qu et al, 2002;Feldman, Schmidt and Sohler, 2013) and shown to provide strong statistical guarantees .…”
Section: Discussionmentioning
confidence: 99%